Comparison of treatment results of subdenture stomatitis treated with soft tissue conditioners and hard autopolymerizing reliners - Dairo Javier Marín-Zuluaga; Eliana Maritza Álvarez-Tovar; Juliana Katherine Rojas-García (Universidad de Antioquia, 2009)
Introduction: the use of dentures usually leads to inflammation of soft tissues, this condition must be treated before making a new denture. Soft materials are generally used for this purpose, but they must be changed periodically in order to maintain its properties, this in turn affects the quality of the denture and increases costs. In order to determine if there is a difference in the resolution of sub prosthesis stomatitis (SS), a clinical examination after a month´s use of a tissue conditioner and an autoploymerizing reline material was carried out. Methods: the sample consisted of 32 patients from the geriatric dental clinic of Universidad Nacional de Colombia during 2005 who were using upper complete dentures and presented SS. A culture of their palates was taken in order to determine the presence of Candida albicans. An oral pathologist classified the severity of SS. The dentures were divided in halves, applying tissue conditioner in one halve and autopolymerizing reline material in the other one (Coe Comfort and Kool Liner g. c.). Two dentists previously calibrated in the classification of SS evaluated the patients for a period of four weeks. At the time of evaluation the dentists did not know which material have been applied in each halve. Photographs were taken during each evaluation. Materials were changed weekly during the period of treatment. Results and conclusions: autopolymerizing materials are an alternative for the treatment of SS. Every denture must be re-adapted before changing it in order to improve seating.